2002
DOI: 10.1029/2001gl013656
|View full text |Cite
|
Sign up to set email alerts
|

Applying artificial neural network to the short‐term prediction of electron density structure using GPS occultation data

Abstract: [1] Artificial neural network (ANN) is used for assimilating of GPS ionospheric occulted data in order to take full advantage of the abundant GPS occulted data. A feedforward, full-connected network is chosen based on the back-propagation algorithm. Universal time, latitude, longitude, height, Kp index, and F 10.7 solar flux are chosen as the input vectors of the network while the electron density as the output vectors. The GPS occultation data on May 24th, 1996 were taken as training samples to train an ANN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…At the same time, Cander and Lamming (1997) use the multi-layer perceptron to model different ionospheric parameters. Then, in 2002, Zeng et al (2002) used GPS occultation data to build an artificial neural network for short-term prediction of electron density structure. Habarulema et al (2007) developed a NN prediction model for the TEC of the global positioning system over South Africa in 2007.…”
mentioning
confidence: 99%
“…At the same time, Cander and Lamming (1997) use the multi-layer perceptron to model different ionospheric parameters. Then, in 2002, Zeng et al (2002) used GPS occultation data to build an artificial neural network for short-term prediction of electron density structure. Habarulema et al (2007) developed a NN prediction model for the TEC of the global positioning system over South Africa in 2007.…”
mentioning
confidence: 99%
“…In addition, many research has also achieved good results with few samples. [55][56][57][58] Therefore, we think that 1700 samples are not too many, they can also reflect a certain law of wind field change.…”
Section: B Training Processmentioning
confidence: 99%
“…Zeng et al. (2002) used Global Positioning System (GPS) occultation data to predict the ionospheric electron density. The results showed that the ANN was an effective method for establishing an ionospheric prediction model.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction results proved the promising prospect of artificial neural networks in ionospheric prediction. Zeng et al (2002) used Global Positioning System (GPS) occultation data to predict the ionospheric electron density. The results showed that the ANN was an effective…”
mentioning
confidence: 99%